Wind’s Element in the Artistic World of Ivan Bunin: Semantic Strategies and Dominants - Nurullina, Guzel M.; Yuan, Tao; Sajakhova, Lena G.; Usmanova, Liliya A. (Journal of History Culture and Art Research, 2017)
The article considers the principles of systematization of the outer world in the author’s individual consciousness of I.A. Bunin and presents the description of personal imaginative nominations of elemental phenomena of nature. The research is based on the synthesis of traditional and modern methods of analysis for realization of a literary word: component, discourse-text analysis of names, as well as cognitive-hermeneutic text analysis, which made it possible to set up a correspondence existing between the units of the text, the information coded by them and the mental structures behind this information, or their elements by studying the character of the connections between them. The analyzed ways of verbalization of the author’s meanings at the level of contact and distant connections allow to reveal the cognitive-mental and emotive spheres of the writer’s consciousness, and also to interpret the phenomenon of Bunin’s Universe as a complex phenomenon that determines its uniqueness and originality in Russian literature. It is noted that the textual realization of words in literary discourse leads to the integration of various aspects of reality and recreates the author’s perception of the world, based on the inseparable, interpenetrating unity of the objective and subjective, the logical and sensual, the rational and emotional. The presented paradigm of the images of wind elicits the properties of its prototype and explicates new properties and attributes of the denotation on the basis of its systemic and non-systemic relationships arisen in the author’s consciousness. On the basis of the considered complex of associativesingsof the element of wind, the authors reveal Bunin’s understanding of the semantic multidimensionality of being, the complexity and versatile relations between man and the world.